Primary DNA damages in taxi drivers with traffic related air pollution exposure: results of comet assay test - Vida Rezaei hachesu (طب کار, 2017)
Introduction: Several studies have shown that DNA damages increase the risk of diseases such as cancer. One of the tests that used to assess the damage to DNA is Comet Assay. In this study, the initial damage caused by exposure to traffic-related air pollution was studied.